Police interview of suspects in China: Developments and analyses - Zeng, Fanjing (International journal of police science & management, 2021)
This article investigates the power dynamics in police interviews with suspects in China by examining a real-life sample. It first overviews some recent developments and legislation in China regarding police interviewing of suspects, followed by outlining the linguistic and psychological research upon which the analyses are based. The interviews are examined using critical discourse analysis that reveals the high-power position of the Chinese police in suspect interviews. However, the large proportion of open questions found in the interviews is encouraging, as this suggests that regulations outlawing use of evidence obtained by torture or other illegal means are taking effect. This article is the first to empirically examine actual Chinese police interviews with suspects, providing valuable insights for theories and practice.